Embankment vibration characteristics using ground motion records and ambient noise measurements, Briones Dam, California - Ilgac, Makbule; Athanasopoulos-Zekkos, Adda; Ktenidou, Olga-Joan; Nweke, Chukwuebuka Chukwuemeka; Peterson, Kyle; Kayen, Robert E. (JAPANESE GEOTECHNICAL SOC, 2025)
Investigating the seismic response of earth embankment dams is crucial for assessing the safety of existing dams and guiding new design procedures. The dam fundamental frequency (f(0)) is a critical parameter in the dynamic response of dams and can be evaluated using seismic recordings through Horizontal-to-Vertical Spectral Ratio (HVSR) and Standard Spectral Ratio (SSR) methods. This study focuses on assessing the vibration characteristics of Briones Dam, a 78 m-tall earth embankment dam located in the Bay Area in Northern California. First, earthquake-based Horizontal-to-Vertical Spectral Ratio (eHVSR) was estimated by dividing the horizontal records by the vertical components, and the SSR was determined by comparing crest recordings with those from the abutment. Additionally, a field test program was conducted to collect ambient noise measurements at Briones Dam, allowing for the calculation of microtremor-based HVSR. The fundamental frequency was estimated using three empirical methods: mHVSR (0.7-1 Hz), eHVSR (0.9-1.1 Hz), and SSR (1.2 Hz). The median fundamental frequency of the dam is estimated to be approximately 1 Hz at the center of the dam crest. The slight variations among these three methods suggest the need for further investigations that consider the geological and geotechnical conditions of the dam. (c) 2025 Japanese Geotechnical Society. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http:// creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Earth dam; Microtremor; Earthquake; Fundamental frequency; Earthquake based horizontal-to-vertical spectral ratio (eHVSR); Microtremor based horizontal-to-vertical spectral ratio (mHVSR); Standard Spectral Ratio (SSR); Dynamic response; SHEAR-WAVE VELOCITY; SEISMIC RESPONSE; EARTH DAMS; SITE AMPLIFICATION; DYNAMIC-ANALYSES; SPECTRAL RATIOS; FREQUENCY; HVSR; VALLEY; Engineering; Geology